Problem Based Learning Berbasis Media Manipulatif, Media Gambar dan Non Media untuk Kemampuan Koqnitif dan Aktivitas Belajar Siswa - Hajar, Dwi Fatmi; Risnanosanti, Risnanosanti; Khasardi, Khasardi (JOEAI (Journal of Education and Instruction), 2026)
This research aims to determine 1) Differences in students' cognitive abilities using the Problem Based Learning Model based on manipulative media, image and conventional media in mathematics learning at the Uswatun Hasanah integrated Islamic elementary school. 2) Differences in student learning activities using the Problem Based Learning Model based on manipulative media, image media and conventional mathematics learning in the integrated Islamic elementary school Uswatun Hasanah, 3)Which learning model is more effective for improving students' cognitive abilities and student learning activities. This research uses quasi-experimental research. The results of this research show that there are differences in students' cognitive abilities and activities in implementing the Problem Based Learning model based on manipulative media, image media and conventional media. Problem Based learning based on manipulative media and image media is better than conventional, but manipulative media is more suitable than image media for teaching mathematics with comparative material.   Keywords: Activities, Cognitive Abilities, Problem Based Learning  (PBL)